NEEDS ANALYSIS-BASED ENGLISH SYLLABUS FOR COMPUTER SCIENCE STUDENTS OF BINA DARMA UNIVERSITY - Ira Septiana; Ismail Petrus; Rita Inderawati (University of Kuningan, 2020)
This study aims to design an appropriate English syllabus for computer science students of Bina Darma University. This study analyzes the needs of students using Target Situation Analysis (TSA), Deficiency Analysis (DA), and Strategy Analysis (SA). Descriptive analysis approach method is used in this study. There were 61 students in the second semester of Bina Darma Palembang majoring in computers, 1 lecturer and director of the institute involved in this study. Data were collected obtained from questionnaires, interview, observation, and documents review. The results show that the target needs are speaking and writing skill. The two language basic skills get a large portion in the preparation of the English syllabus. In addition, students need a learning process to focus more on practice than theory. The learning process also needs to be integrated with technology to make classroom activities more interesting. Finally, this study proposes a syllabus that is recommended to use in the institution.